2006
DOI: 10.1002/ajmg.a.31416
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of various genetic approaches in patients with unexplained developmental delay or mental retardation

Abstract: The underlying cause of mental retardation remains unknown in up to 80% of patients. As chromosomal aberrations are the most common known cause of mental retardation, several new methods based on FISH, PCR, and array techniques have been developed over recent years to increase detection rate of subtle aneusomies initially of the gene rich subtelomeric regions, but nowadays also genome wide. As the reported detection rates vary widely between different reports and in order to compare the diagnostic yield of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
278
2
59

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 382 publications
(351 citation statements)
references
References 54 publications
12
278
2
59
Order By: Relevance
“…After digestion, an adaptor was linked to the restricted fragments, the reaction was diluted 4Â and the fragments were amplified by PCR. After purification using Magnetic Beads (Agencourt Bioscience Corporation, Beverly, MA, USA), 90 mg of PCR products was fragmented and end labeled using 30 U/ml of terminal deoxynucleotidyl transferase, and then hybridized for [16][17][18] h to the Affymetrix 6.0 chip at 491C in a GeneChip Hybridization Oven 640 (Affymetrix). The chips were washed, stained in GeneChip Fluidic Station 450 (Affymetrix) and scanned with Scanner 3000 7G (Affymetrix).…”
Section: Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…After digestion, an adaptor was linked to the restricted fragments, the reaction was diluted 4Â and the fragments were amplified by PCR. After purification using Magnetic Beads (Agencourt Bioscience Corporation, Beverly, MA, USA), 90 mg of PCR products was fragmented and end labeled using 30 U/ml of terminal deoxynucleotidyl transferase, and then hybridized for [16][17][18] h to the Affymetrix 6.0 chip at 491C in a GeneChip Hybridization Oven 640 (Affymetrix). The chips were washed, stained in GeneChip Fluidic Station 450 (Affymetrix) and scanned with Scanner 3000 7G (Affymetrix).…”
Section: Controlsmentioning
confidence: 99%
“…15 Genetic causes account for 17.4-47.1% of cases, with reported frequencies also varying on the basis of the different techniques used for analysis. 15,16 Several years ago, microarray platforms were used for the first time in clinical genetics, showing that abnormalities in genomic copy number account for about 10-15% of patients affected by MR, especially when it is associated with multiple congenital anomalies (MCA) and/or dysmorphism. 17 Microarrays represent a robust and high-resolution method of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite this, more than 60% of patients have no identifiable genetic cause. 3 The recent introduction of next-generation sequencing technologies has opened new possibilities, making the detection of causal variants more economical and faster. Recent studies have revealed that a significant proportion of sporadic ID might be attributable to de novo mutations, 4,5 whereas only a small number has shown recessive inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…In a representative study, Rauch et al 2 showed that 15% of the cases of ID are due to cytogenetic anomalies, and that further 15% are due to submicroscopic aberrations. X-chromosomal mutations are possibly the cause in about 10% of the cases.…”
Section: Introductionmentioning
confidence: 99%